c * -Supplemented subgroups and p -nilpotency of finite groups - Wang, Youyu; Wei, H. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
A subgroup $H$ of a finite group $G$ is said to be $c^{*}$-supplemented in $G$ if there exists a subgroup $K$ such that $G = HK$ and $H ⋂ K$ is permutable in $G$. It is proved that a finite group $G$ that is $S_4$-free is $p$-nilpotent if $N_G (P)$ is $p$-nilpotent and, for all $x ∈ G \backslash N_G (P)$, every minimal subgroup of $P ∩ P^x ∩ G^{N_p}$ is $c^{*}$-supplemented in $P$ and (if $p = 2$) one of the following conditions is satisfied: (a) every cyclic subgroup of $P ∩ P^x ∩ G^{N_p}$ of order 4 is $c^{*}$-supplemented in $P$, (b) $[Ω2(P ∩ P^x ∩ G^{N_p}),P] ⩽ Z(P ∩ G^{N_p})$, (c) $P$ is quaternion-free, where $P$ a Sylow $p$-subgroup of $G$ and $G^{N_p}$ is the $p$-nilpotent residual of $G$. This extends and improves some known results.